ASSISTIVE E-MATH TOOLS: BOON OR BANE? - BUCU, ALJON S. (International Journal of Psychosocial Rehabilitation, 2020)
This study reinforced the use of handheld gadgets and applications designed to increase level of proficiency by making them more educational, that is, students and teachers integrate assistive electronic or e- math tools in deepening and elaborating discussions in Basic Calculus. Some of these tools composed of Geogebra, Mathway, and Photomath which made the instructions more interactive and comprehensive. Furthermore, it sought to find answers to the following (a). students’ level of proficiency in the first grading period before using the assistive e-math tools, (b) the students’ level of proficiency in the second grading period after using the assistive e- math tools, (c) significant difference between the students’ level of proficiency before and after using the assistive e-math tools and (d) effect size of the difference of using the assistive e-math tools to the students’ level of proficiency.Quantitative research design was employed particularly one-group pretest-posttest design wherein a pretest observation of the dependent variables is made before implementation of the treatment to the selected group, the treatment is administered, & finally a posttest observation of dependent variables is carried out to assess the effect of treatment on the group. One-hundred Nineteen (119) Grade 11 students for school year 2018-2019 formed the respondents of the study. Frequency, Percentage, and mean for descriptive analysis while ANOVA for single group likewise eta squared and Cohen’s Guidelines were used for the interpretation of inferential question. Findings revealed that integrating the assistive e-math tools in the instructional delivery or in the teaching and learning process produced a moderate effect or difference. Students who were exposed to this intervention improved its academic performance or level of proficiency; thus, assistive e-math tools are considered Boon not Bane. This study finally concludes that teachers must positively use the available tools or technologies that students have in order to optimize learning outcomes.